Female firefighters’ increased risk of occupational exposure due to ill-fitting personal protective clothing - McQuerry, Meredith; Kwon, Cassandra; Poley-Bogan, Madeline (Frontiers in Materials, 2023)
Despite the growing female firefighter population, firefighting gear was originally designed with only the male human form in mind. As a result, women in the fire service experience issues of improper fit and injuries at rates much higher than their male counterparts. Areas of ill-fit, specifically in interfaces, can increase the risk of occupational exposure for women in the fire service. The purpose of this research was to determine fit and sizing issues of personal protective clothing (PPC) to improve female firefighters’ comfort, mobility, and safety. A mixed methods approach was adopted including a nationwide questionnaire, end user focus groups, and remote three-dimensional body scanning of 189 female structural and wildland firefighters. In addition to this study gathering and creating the first and largest U.S. female firefighter anthropometric database, results indicate the majority of female firefighters are dissatisfied with the fit of their PPC and believe it negatively impacts their thermal, liquid, and smoke/particulate protection. Large discrepancies between structural and wildland female sizing systems were identified with the greatest opportunity for fit improvement occurring in wildland PPC.